The Effect of Breast Care Actions on Infant Breast Milk Adequacy in Post-Partum Mothers at the Banyumas Regional General Hospital - Eka Susi Indriani Eka; Tin Utami; Linda Yanti (Universitas Ibn Khaldun Bogor, 2024)
Breast milk plays an important role in a child's growth and development. Breast milk is the ideal food for infants that provides age-appropriate nutrients, immunological factors and anti-bacterial substances. A baby's growth is greatly influenced by the release of breast milk. Rapid growth can occur at the age of 2 weeks, 6 weeks and 3 months at which time more breast milk is needed. The adequacy of breast milk produced by post partum mothers is one of the needs for infants, the lack of breastfeeding will have an impact on infant growth and development. One of the efforts that can be made to increase the smooth production of breast milk is breast care. Quasy Experimental research design with One Group Pre Test-Post Test Design type. The sample in this study were 24 respondents using accidental sampling technique. Data analysis was determined by pairedsample t-test. The results of the paired sample t- test, showed a p-value of 0.000 (p <0.05), so it can be concluded that there is a significant influence, breast care actions on the adequacy of infant breast milk in post partum mothers at Banyumas Hospital. This study is expected to add information to mothers about the effect of breast care actions on the adequacy of infant breast milk in post partum mothers.